The Perspective of Turkey in the Post Occupancy Evaluation Studies - Işıklar Bengi, Sena; Topraklı, Abdurrahman Yağmur (Periodica polytechnica. Architecture, 2020)
From past to present, the evaluation of structures has been the subject of both academic studies and practices through different systematic methods. One of these methods is the "Post Occupancy Evaluation". The method, whose first implementations date back to the 1960s, enables to process hard-to-evaluate data that is based on the dynamic structure of the user. It focuses on detecting the gaps between user satisfaction and physical environment. POE provides advantages in certain subjects such as comprehending the relationship among the use, attitude, and evaluation of the building performance, and making conscious decisions about the future building designs. In this study, a review was conducted about the definition and advantages of the "Post Occupancy Evaluation" as well as its introduction into the literature and its place in the literature. Subsequently, progressing further, the studies of this model in Turkey were presented. Concerning the studies conducted since the evaluation was introduced into the academy in Turkey, the qualifications, objectives and types of buildings they focused on were cited. It was determined that the majority of the studies were conducted on several building types, and mainly focused on design evaluations, user evaluations, energy performance evaluations, and IEQ evaluations that are defined as the direct objectives of the POE studies. By evaluating the findings, the deficiencies were discovered in the implementation of the method in Turkey and the development of country-specific evaluation protocols, the importance of the evaluation method was emphasized, and the need to improve the deficiencies was stated.